TRENDS IN CONCOMITANT MENISCAL SURGERY AMONG PEDIATRIC PATIENTS UNDERGOING ACL RECONSTRUCTION: AN ANALYSIS OF ABOS PART II CANDIDATES FROM 2000-2016. Issue 4 (28th April 2020) - Cruz, Aristides I.; Gao, Burke; Ganley, Theodore J.; Shea, Kevin; Beck, Jennifer; Ellis, Henry
Background: Rates of ACL reconstruction among pediatric/adolescent patients are increasing. Limited knowledge exists about population level rates of concomitant meniscal surgery in this population. Hypothesis/Purpose: To examine trends in concomitant meniscus procedures and describe short-term complications in pediatric/adolescent patients undergoing ACL reconstruction. We hypothesized that overall meniscal surgery rates are increasing, and that the likelihood of performing meniscal repair or meniscectomy is associated with patient and surgeon specific factors. Methods: ACL procedures in patients <19 years reported by ABOS Part II examination candidates from 2000-2016 were queried. Regression models examined associations between patient & surgeon characteristics, year of surgery, follow-up time, meniscal procedure type, and number and type of complications. Results: 9, 766 cases were identified. Females represented 46% (n=4, 468). Average patient age was 16.1 years (SD: 1.62, range 0-18). The rate of concomitant ACL-meniscal procedures increased from 2000-2016 (49%-60%; p=0.005). Surgeons with sports medicine (+7.0%) or pediatric orthopaedics fellowship (+6.6%) training had a higher likelihood of reporting a concomitant ACL-meniscus procedure (p=0.003; p=0.006, respectively). Sports medicine (+3.0%) trained surgeons were more likely to perform meniscus repair vs. meniscectomy (p=0.016). Younger patient age was associated with increased likelihood of undergoing meniscus repair vs. meniscectomy. Overall reported complication rate was 12.8%. Notable reported complications included: infection (1.61%), arthrofibrosis (1.14%), and DVT/PE (0.11%). Sports medicine and pediatric orthopaedic fellowship training were associated with higher rates of reporting post-operative stiffness/arthrofibrosis. Conclusions: Among ABOS Part II candidates, concomitant ACL-meniscus surgery has become more common than isolated ACL procedures. Surgeries involving sports medicine fellowship trained surgeons and younger patients were associated with increased rates of meniscus repair vs. meniscectomy. Pediatric orthopaedics and sports medicine training were associated with a higher likelihood of being involved in a concomitant ACL-meniscus procedure and also reported a higher incidence of post-operative stiffness/arthrofibrosis. : Figure 1. Trends in total isolated ACL vs. total concomitant ACL-meniscus surgery, by year of procedure. The Y-axis represents the frequency of a target case type as a proportion of the total number of ACL procedures completed in a given year. Figure 2. Trends in type of concomitant meniscus surgery, by year of procedure. The Y-axis represents the frequency of a target case type as a proportion of the total number of concomitant ACL-meniscus procedures completed in a given year.